CONSIDERING AL-GHAZALI'S PHILOSOPHY THINKING AUTHORITY - Teguh Purnomo Putra (UIN Syarif Hidayatullah Jakarta, 2021)
Abstract. The reputation and authority of al-Ghaza li in Islamic thought has had a profound influence as well as is controversial and ambivalent. His character covers almost all scientific disciplines in Islam. In the field of philosophy, the response to his thinking generated controversy that lasted for centuries. On the one hand, he is assumed to be a central figure for the decline of Islamic thought, especially philosophy, and is considered the most successful thinker in positioning philosophy proportionally in the Islamic world on the other. This paper discusses the philosophical thinking of al-Ghaza li, his criticisms of the thoughts of previous philosophers, and responses to his thoughts in the hope that they can provide conclusions that are quite